Secrets of a Pepto Bismol casa. - Temblador, Alexandra (My University, 2014)
Secrets of a Pepto Bismal Casa explores the journey of a young, Mexican American girl named Martha in Laredo, Texas, in 1990. The novel is set in first person point-of-view and is split into two threads--what occurs in 1990, the past, and what occurs in the present, some forty years later. Martha is abandoned by her mother in Laredo with her grandmother, who doesn't speak English and who Martha does not know. Abuela, Martha's grandmother, is a curandera, a Mexican folk healer whose position in the community is that of physical curer, spiritual guide, and secret-keeper of her patients. However, Martha discovers that these are not the only secrets being kept. Many secrets are being protected by her family, all of which seem to center of her mother's escape from Laredo eighteen years earlier and the reason for her mother's current disappearance.
Keywords: Families; Grandmothers; Healers; Mexican Americans